2021
DOI: 10.1097/phm.0000000000001818
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Access to Therapies and Impact on Well-Being During the COVID-19 Pandemic for Children With Motor Impairment and Their Caregivers

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Nearly half of the sample reported decreased exercise participation, which was similar to that reported among children with cerebral palsy in the Midwest U.S. 19 This is an alarming finding because adolescents with cerebral palsy have been found to participate in far lower levels of health-enhancing exercise compared to adolescents without cerebral palsy prior to the pandemic. 16 , 33 As a result of rapid deconditioning, exercise levels have likely reached new lows with concomitant declines in health and physical function as a result of rapid deconditioning.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Nearly half of the sample reported decreased exercise participation, which was similar to that reported among children with cerebral palsy in the Midwest U.S. 19 This is an alarming finding because adolescents with cerebral palsy have been found to participate in far lower levels of health-enhancing exercise compared to adolescents without cerebral palsy prior to the pandemic. 16 , 33 As a result of rapid deconditioning, exercise levels have likely reached new lows with concomitant declines in health and physical function as a result of rapid deconditioning.…”
Section: Discussionsupporting
confidence: 52%
“…10 In the Midwest U.S., a study including 102 children with motor impairment reported a 36% reduction in receiving therapies, as well as a substantial proportion of children who reported increased mental stress. 19 The present study added to this knowledge by providing a more in-depth evaluation of COVID-19 affected lifestyle behaviors. Further research is necessary to explain reductions in mental health and physical activity behavior and, most importantly, how to improve these issues among adolescents with cerebral palsy in the post COVID-19 era.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Missed practices appeared to be at least partially attributable to pandemic related precautions and circumstances such as exposure to someone infected with COVID-19. In addition, following a pause in certain medical care for the year prior (Sutter et al, 2021 ) families may have been catching up on medical appointments for routine care such as eye exams or physiatry visits. Children with movement challenges have higher healthcare needs in general, and future expectations for attendance may need to take some of these factors into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Such protective measures and restrictions have directly affected community-based services that children with disabilities often rely on, for example, health care systems, disability services, institutional environments, and schools [ 4 ]. People with disabilities and their families may be disproportionately affected by disrupted access to health care and community support services in these extreme circumstances, resulting in increased stress and anxiety and decreased outdoor and physical activity [ 5 , 6 ]. The suffering and stress might be even higher for children with severe disabilities, such as children with cerebral palsy (CP) or children relying mainly on wheelchairs for their mobility, in pandemic situations because it is almost impossible for them to ambulate outside independently and because they are more likely to experience access limitations [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%